Dendritic imidazole ionic polymer containing hexafluorophosphoric acid anions as well as preparation method and application thereof

By forming a branched hexafluorophosphate anion-containing imidazole ion polymer with a dense adsorption layer on the copper surface, the problems of complex preparation of existing copper corrosion inhibitors and poor corrosion inhibition effects are solved, and efficient corrosion inhibition of copper in an inorganic acid environment is achieved.

CN119638988APending Publication Date: 2025-03-18DALI BUREAU OF ULTRA HIGH VOLTAGE TRANSMISSION CO CHINA SOUTHERN POWER GRID CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411825867.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing copper organic corrosion inhibitor preparation process in inorganic acids is complex, with high requirements and poor corrosion inhibition effects, making it difficult to effectively prevent the corrosion of copper by inorganic acid media.

Method used

A polymer with high yield and excellent corrosion inhibition effect was prepared by a branched imidazole ionic polymer containing hexafluorophosphate anion, and a stirring reaction was carried out by precipitation method at room temperature. This polymer can spontaneously form a dense adsorption layer in a variety of organic solvents, effectively inhibiting the corrosion of copper by inorganic acid medium.

Benefits of technology

It realizes efficient corrosion inhibition of copper in an inorganic acid environment, with mild conditions, simple operation, fast reaction, high yield, easy to obtain raw materials, and suitable for a wide range of application scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638988A_ABST
    Figure CN119638988A_ABST
Patent Text Reader

Abstract

The invention relates to a dendritic imidazole ionic polymer containing hexafluorophosphoric acid anions and a preparation method thereof. The dendritic imidazole ionic polymer containing hexafluorophosphoric acid anions is prepared from a dendritic imidazole ionic polymer containing bromide ions and lithium hexafluorophosphate through a precipitation method. The preparation method comprises the following steps: S1, dissolving: weighing the dendritic bromine ion-containing imidazole ionic polymer and lithium hexafluorophosphate according to the proportion, respectively adding into acetone, and stirring for dissolving for later use; s2, stirring reaction: mixing the two obtained solutions, and stirring at room temperature for 20-40 minutes to obtain a white precipitate; s3, suction filtration and washing: carrying out suction filtration and washing on the obtained white precipitate at least once to obtain a purified white solid; and S4, vacuum drying: carrying out vacuum drying on the purified white solid at room temperature for 5-7 hours to obtain a target product. The preparation method has the characteristics of simplicity, high yield, excellent corrosion inhibition effect and the like, and can be widely applied to the field of corrosion inhibition of copper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper corrosion inhibition, and in particular to a type of branched imidazole ion polymer containing hexafluorophosphate anions, a preparation method and an application thereof. Background Art

[0002] As an important heavy metal, copper is used in many fields because of its excellent thermal and electrical conductivity. However, copper rust is produced by complex chemical reactions between O2, CO2, and H2O on the copper surface, including compounds such as copper oxide or hydroxide or bicarbonate or carbonate. Therefore, inorganic acid solutions (such as H2SO4 and HCl solutions) are often used for pickling to remove copper rust. However, copper is easily corroded in inorganic acidic media, leading to many serious problems, such as equipment damage, environmental pollution, and threats to life. Therefore, copper corrosion in inorganic acid solutions must be prevented.

[0003] The existing organic corrosion inhibitors for copper in inorganic acids have the disadvantages of complex preparation process, high requirements for preparation conditions, and poor corrosion inhibition effect.

[0004] Therefore, it is necessary to propose a type of branched imidazole ion polymer containing hexafluorophosphate anion and a preparation method and application, which has the characteristics of simple preparation, high yield, excellent corrosion inhibition effect, etc., and can be widely used in the field of copper corrosion inhibition in inorganic acid environment. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a type of branched imidazole ion polymer containing hexafluorophosphate anions, which has sufficient raw material sources, fast preparation, high yield and good corrosion inhibition effect, and can be widely used in the corrosion inhibition of copper in an inorganic acid environment.

[0006] In order to solve the above technical solution, the technical solution of the present invention is: the branched imidazolium ion polymer containing hexafluorophosphate anions is prepared by using a branched imidazolium ion polymer containing bromide ions and lithium hexafluorophosphate through a precipitation method.

[0007] By adopting the above technical scheme, the branched imidazole ion polymer DIP [Br - ] and lithium hexafluorophosphate Li[PF6 - ] as the starting material, acetone as the reaction solvent, a precipitation method is adopted to obtain a precipitate by stirring at room temperature, and then the precipitate is further washed with acetone and dried to obtain a type of branched imidazole ion polymer containing hexafluorophosphate anion. The conditions are mild, the operation is simple, the reaction is fast, the yield is high, and the raw materials are easy to obtain. The branched imidazole ion polymer containing hexafluorophosphate anion DIP[PIF6 -] can spontaneously form a dense adsorption layer on the copper surface in a variety of organic solvents such as DMSO, DMF and CH3CH2OH, thereby effectively inhibiting the corrosion of copper by inorganic acid media.

[0008] Preferably, the mass of the branched imidazolium ion polymer containing bromide ions in the branched imidazolium ion polymer containing hexafluorophosphate anions is 0.2 to 4.8 g, and the mass of lithium hexafluorophosphate is 0.6 to 7.6 g.

[0009] Preferably, acetone is used as the reaction solvent, and the amount of acetone used is 5 to 95 mL.

[0010] Preferably, the mass of the branched imidazolium ion polymer containing bromide ions in the branched imidazolium ion polymer containing hexafluorophosphate anions is 1.2 g, and the mass of lithium hexafluorophosphate is 2.4 g.

[0011] The technical problem that the present invention also solves is to provide a method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anions, which is simple and has high yield.

[0012] In order to solve the above technical solution, the technical solution of the present invention is: a method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anion, comprising the following steps:

[0013] S1 dissolution: weigh the branched bromide-containing imidazole ion polymer and lithium hexafluorophosphate according to the ratio, add them into acetone respectively, stir and dissolve, and set aside;

[0014] S2 stirring reaction: mixing the two solutions obtained in step S1 and stirring at room temperature for 20 to 40 minutes to obtain a white precipitate;

[0015] S3: Filtration and washing: filtering and washing the obtained white precipitate at least once to obtain a purified white solid;

[0016] S4 vacuum drying: the purified white solid is vacuum dried at room temperature for 5 to 7 hours to obtain the target product, a type of branched imidazole ion polymer containing hexafluorophosphate anion.

[0017] Adopting the above technical solution, HIM[Br - ] and Li[PIF6 - ] were dissolved in acetone, and HIM[Br - ] solution was added dropwise to the Li[PF6] solution to form a precipitate, the precipitate was filtered, washed with acetone, and the obtained HIM[PIF6 - ] for drying. -] and lithium hexafluorophosphate (Li[PF6]) through ion exchange reaction to obtain the target ion polymer HIM[PIF6 - The preparation method has mild conditions, simple operation, fast reaction and high yield.

[0018] Preferably, the specific steps of step S3 are:

[0019] S31 filtration: filtering the white precipitate obtained in step S2 to obtain a white solid;

[0020] S32 washing: washing the white solid obtained in step S31 with acetone;

[0021] S33 re-filtration: The precipitate in step S32 is re-filtered to obtain a white solid.

[0022] Preferably, in step S2, the mixture is stirred at room temperature for 30 minutes, and a white precipitate is obtained after the reaction is completed.

[0023] Preferably, in step S4, vacuum drying is performed at room temperature for 6 hours to obtain the target product.

[0024] The technical problem that the present invention needs to solve is to provide an application of a type of branched imidazole ion polymer containing hexafluorophosphate anions.

[0025] In order to solve the above technical solution, the technical solution of the present invention is: the branched imidazole ion polymer containing hexafluorophosphate anion is used as a copper corrosion inhibitor.

[0026] This type of branched imidazolium ion polymer containing hexafluorophosphate anions DIP[PIF6 - ] can spontaneously form a dense adsorption layer on the copper surface in a variety of organic solvents such as DMSO, DMF and CH3CH2OH, thereby effectively inhibiting the corrosion of copper by inorganic acid media.

[0027] Preferably, the branched imidazolium ion polymer containing hexafluorophosphate anion is used as a corrosion inhibitor for copper in an inorganic acid medium.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The copper corrosion inhibitor DIP[PIF6 of the present invention - ] is a mixture of DIP[Br-] and lithium hexafluorophosphate Li[PF6 - ] is prepared as the starting material, with mild conditions, simple operation, fast reaction, high yield, and easy to obtain raw materials;

[0030] (2) The copper corrosion inhibitor DIP[PIF6 of the present invention -] It can spontaneously form a dense adsorption layer on the copper surface in a variety of organic solvents such as DMSO, DMF and CH3CH2OH, effectively inhibiting the corrosion of copper by inorganic acid media;

[0031] (3) The copper corrosion inhibitor DIP[PIF6 of the present invention - ]'s corrosion inhibition application is simple and quick. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The chemical structure diagram of a type of branched imidazolium ion polymer containing hexafluorophosphate anion of the present invention;

[0033] Figure 2 The hydrogen nuclear magnetic spectrum of a type of branched imidazolium ion polymer containing hexafluorophosphate anion of the present invention;

[0034] Figure 3 The carbon NMR spectrum of a type of branched imidazolium ion polymer containing hexafluorophosphate anions of the present invention;

[0035] Figure 4 The scanning electron microscope images of copper after being corroded in 0.5M sulfuric acid in the application example of the present invention; 4-1 is copper just after being polished; 4-2 is blank copper after being immersed in 0.5M sulfuric acid for 6 hours; 4-3 is copper adsorbed with target ion polymer after being immersed in 0.5M sulfuric acid for 6 hours;

[0036] Figure 5 For the blank copper and adsorbed HIM [PIF6 in the application example of the present invention - ] Atomic force three-dimensional map (AFM surface morphology map) of copper and its height distribution map: Among them, Figure 5 (a) and (b) are blank copper; Figure 5 (c) and (d) are blank copper samples corroded in 0.5M sulfuric acid at room temperature for 48 hours; Figure 5 (e) and (f) adsorption of HIM[PIF6 - ] was immersed in 0.5 M sulfuric acid for 48 h. DETAILED DESCRIPTION

[0037] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the protection scope of the present invention.

[0038] Embodiment: The branched imidazolium ion polymer containing hexafluorophosphate anions is prepared by using a branched imidazolium ion polymer containing bromide ions and lithium hexafluorophosphate by precipitation method. The mass of the branched imidazolium ion polymer containing bromide ions in the branched imidazolium ion polymer containing hexafluorophosphate anions is 0.2-4.8 g, and the mass of the lithium hexafluorophosphate is 0.6-7.6 g. Acetone is used as a reaction solvent, and the amount of acetone used is 5-95 mL. The chemical structure of the branched imidazolium ion polymer containing hexafluorophosphate anions is shown in FIG. Figure 1 shown.

[0039] Method Example: The preparation method of the branched imidazole ion polymer containing hexafluorophosphate anion comprises the following steps:

[0040] S1 dissolution: weigh the branched bromide-containing imidazole ion polymer and lithium hexafluorophosphate according to the ratio, add them into acetone respectively, stir and dissolve, and set aside;

[0041] S2 stirring reaction: the two solutions obtained in step S1 are mixed and stirred at room temperature (25° C.) for 20 to 40 minutes to obtain a white precipitate;

[0042] S3: Filtration and washing: filtering and washing the obtained white precipitate at least once to obtain a purified white solid;

[0043] The specific steps of step S3 are:

[0044] S31 filtration: filtering the white precipitate obtained in step S2 to obtain a white solid;

[0045] S32 washing: washing the white solid obtained in step S31 with acetone twice;

[0046] S33: re-filter the precipitate in step S32 to obtain a white solid;

[0047] S4 vacuum drying: the purified white solid is vacuum dried at room temperature for 5 to 7 hours with a vacuum degree of 0 Pa; the target product, a type of branched imidazole ion polymer containing hexafluorophosphate anions, is obtained.

[0048] Specific embodiment: The preparation method of this type of branched imidazole ion polymer containing hexafluorophosphate anion includes the following steps:

[0049] S1 dissolution: weigh 1.2g of branched bromide-containing imidazole ion polymer DIP[Br-] and 2.4g of lithium hexafluorophosphate Li[PF6-] according to the ratio, add them into acetone respectively, stir and dissolve, and set aside;

[0050] S2 stirring reaction: the two solutions obtained in step S1 are mixed and stirred at room temperature for 30 minutes to obtain a white precipitate;

[0051] S3 filtration and washing: the obtained white precipitate is filtered and washed twice to obtain a purified white solid;

[0052] The specific steps of step S3 are:

[0053] S31 filtration: filtering the white precipitate obtained in step S2 to obtain a white solid;

[0054] S32 washing: washing the white solid obtained in step S31 with acetone;

[0055] S33: re-filter the precipitate in step S32 to obtain a white solid;

[0056] S4 vacuum drying: The purified white solid was vacuum dried at room temperature for 6 hours with a vacuum degree of 0 Pa to obtain the target product, a type of branched imidazole ion polymer containing hexafluorophosphate anion, weighing 1.76 g.

[0057] NMR 1H spectrum and 13C spectrum are as follows Figure 2 and Figure 3 As shown, the NMR characterization results of DIP[PIF6-] ​​are as follows: 1H-NMR (D6-DMSO, 600MHz) δ (ppm): 7.92-7.59 (N=CH-N), 7.11-6.85 (C=CH-N), 3.93-1.59 (N-CH2-C). 13C-NMR (D6-DMSO, 600MHz) δ (ppm): 140.23, 13 1.27,125.77,123.64,122.37,121.51,119.37,48.43,45.90,33.88,30.74.19F-NMR(D 6-DMSO,600MHz)δ(ppm):-70.82.32P-NMR(D6-DMSO,600MHz)δ(ppm):-69.56.(FT-IR(cm -1 ):3421.41,1664.76,1390.70,1254.91,1104.14,841.99,667.30,557.95.

[0058] The branched imidazole ion polymer containing hexafluorophosphate anion is used as a corrosion inhibitor for copper.

[0059] This type of branched imidazolium ion polymer containing hexafluorophosphate anions DIP[PIF6 -] can spontaneously form a dense adsorption layer on the copper surface in a variety of organic solvents such as DMSO, DMF and CH3CH2OH, thereby effectively inhibiting the corrosion of copper by inorganic acid media.

[0060] The branched imidazole ion polymer containing hexafluorophosphate anion is used as a copper corrosion inhibitor in an inorganic acid medium.

[0061] Application Example: A type of branched imidazole ion polymer DIP [PIF6 - ] in copper corrosion inhibition. - ]Application of copper corrosion inhibition in 0.5M H2SO4 solution.

[0062] (A) The experimental process is as follows:

[0063] The preparation of copper surface test characterization samples is as follows: first, the copper sheet is polished with 400, 800, 1200, 2000, 3000, and 5000 grit sandpaper in sequence, and then the polished copper sheet is ultrasonically treated with acetone and ethanol to remove the polishing residue. The treated copper sheet is immediately placed in 0.100 g / L DIP[PIF6 - ] ethanol solution for 6 hours, and then vacuum dried. - ] were immersed in 0.5 M H2SO4 solution for 48 h and characterized by scanning electron microscopy (SEM).

[0064] Experimental method: To confirm the DIP[PIF6 - ] in 0.5M H2SO4 solution, and the surface morphology of the copper after corrosion was observed by scanning electron microscopy to determine the corrosion inhibition effect of the DIP[PIF6 - ]Inhibition of copper corrosion in 0.5M H2SO4 solution.

[0065] (B) Experimental results: In copper corrosion and corrosion inhibition, observing the morphology of the copper surface through a scanning electron microscope is an intuitive method. The corrosion inhibition effect in 0.5M H2SO4 solution is as follows:

[0066] The copper surface was characterized by SEM microscopy. Figure 4 4-1 in the figure is a blank copper sheet after polishing, and its clear texture structure after polishing can be seen. Figure 4 Figure 4-2 shows the morphology of a blank copper sheet after polishing and corrosion with 0.5M H2SO4 for 48 hours. It can be seen that the surface of the copper sheet is severely corroded and the polishing marks have disappeared. Figure 4 4-3 in the above sample has adsorbed DIP[PIF6 in the range of 0.05 g / L-0.200 g / L- ] copper sheet was immersed in 0.5M H2SO4 solution for 48 hours. It can be seen that the DIP[PIF6 - ] adsorption layer still remains good, indicating that DIP[PIF6 - ] has a good corrosion inhibition effect on copper. At the same time, HIM[PIF6 - ] forms a dense adsorption film on the copper surface, completely covering the copper surface, and even the texture after polishing cannot be observed, indicating that it has a significant corrosion inhibition effect on copper.

[0067] like Figure 5 Blank copper and adsorbed HIM[PIF6 - ] Atomic force 3D image (AFM) of copper and its height distribution map: Figure 5 (a) and (b) are blank copper; Figure 5 (c) and (d) are blank copper samples corroded in 0.5M sulfuric acid at room temperature for 48 hours; Figure 5 (e) and (f) adsorption of HIM[PIF6 - ] copper was immersed in 0.5M sulfuric acid for 48h;

[0068] Figure 5 (a) shows that the copper surface after grinding is relatively flat, and its average roughness Ra is only 4.567nm, and Figure 5 (b) in Figure 1 also shows that its height distribution is close to a straight line, with a height of only about 10 nm. On the contrary, the copper surface after sulfuric acid corrosion is severely corroded, with many large pits and peaks on the surface. Figure 5 As shown in (c), its average roughness Ra reaches 49.897nm, and; Figure 5 (d) in the figure also shows that the height distribution of the copper surface after corrosion shows peaks and valleys above about 160 nm.

[0069] Adsorption of HIM[PIF6 - ]After the copper specimen is immersed in sulfuric acid, the three-dimensional structure imaged by atomic force microscopy is as follows Figure 5 As shown in (e), it can be seen that its surface presents a relatively flat and smooth structure, and its corresponding average roughness Ra and copper surface height are 13.567nm. In addition, its corresponding height distribution Figure 5 (f) in the figure all show curves with height fluctuation within 100nm and are relatively flat.

[0070] For ordinary technicians in this field, the specific embodiments are only illustrative descriptions of the present invention. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned methods. As long as various non-substantial improvements are made using the method concepts and technical solutions of the present invention, or the concepts and technical solutions of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A type of branched imidazolium ion polymer containing hexafluorophosphate anions, characterized in that: The branched imidazole ion polymer containing hexafluorophosphate anions is prepared by using a branched imidazole ion polymer containing bromide ions and lithium hexafluorophosphate through a precipitation method.

2. The branched imidazolium ion polymer containing hexafluorophosphate anion according to claim 1, characterized in that: The mass of the branched imidazolium ion polymer containing bromide ions in the branched imidazolium ion polymer containing hexafluorophosphate anions is 0.2-4.8 g, and the mass of the lithium hexafluorophosphate is 0.6-7.6 g.

3. The branched imidazolium ion polymer containing hexafluorophosphate anion according to claim 1, characterized in that: The method further comprises using acetone as a reaction solvent, wherein the amount of the acetone is 5 to 95 mL.

4. The branched imidazolium ion polymer containing hexafluorophosphate anion according to claim 2, characterized in that: The mass of the branched imidazolium ion polymer containing bromide ions in the branched imidazolium ion polymer containing hexafluorophosphate anions is 1.2 g, and the mass of lithium hexafluorophosphate is 2.4 g.

5. A method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anion, characterized in that: The steps include: S1 dissolution: weigh the branched bromide-containing imidazole ion polymer and lithium hexafluorophosphate according to the ratio, add them into acetone respectively, stir and dissolve, and set aside; S2 stirring reaction: mixing the two solutions obtained in step S1 and stirring at room temperature for 20 to 40 minutes to obtain a white precipitate; S3: Filtration and washing: filtering and washing the obtained white precipitate at least once to obtain a purified white solid; S4 vacuum drying: the purified white solid is vacuum dried at room temperature for 5 to 7 hours to obtain the target product, a type of branched imidazole ion polymer containing hexafluorophosphate anion.

6. The method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anion according to claim 5, characterized in that: The specific steps of step S3 are: S31 filtration: filtering the white precipitate obtained in step S2 to obtain a white solid; S32 washing: washing the white solid obtained in step S31 with acetone; S33 re-filtration: The precipitate in step S32 is re-filtered to obtain a white solid.

7. The method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anion according to claim 5, characterized in that: In step S2, the mixture is stirred at room temperature for 30 minutes, and the reaction is completed to obtain a white precipitate.

8. The method for preparing a type of branched imidazole ion polymer containing hexafluorophosphate anion according to claim 5, characterized in that: In step S4, vacuum drying is performed at room temperature for 6 hours to obtain the target product.

9. An application of a type of branched imidazole ion polymer containing hexafluorophosphate anion, characterized in that: The branched imidazole ion polymer containing hexafluorophosphate anion is used as a corrosion inhibitor for copper.

10. The use of a type of branched imidazolium ion polymer containing hexafluorophosphate anions according to claim 9, characterized in that: The branched imidazole ion polymer containing hexafluorophosphate anion is used as a copper corrosion inhibitor in an inorganic acid medium.